T Cell Avidity and Tumor Immunity: Problems and Solutions - Hurwitz, Arthur A. (Springer Netherlands, 2013)
A potent T cell response is an important component of durable anti-tumor immunity. The quality of the T cell response can, in-part, be measured by the avidity of the T cell for its tumor antigen-expressing target. While convention suggests that raising the avidity of the responding T cells may make for a more potent anti-tumor immune response, the threshold for effective tumor immunity remains unclear, as do some of the adverse effects of an inappropriately high avidity response. In this review, we discuss the relationship between T cell avidity and anti-tumor immunity, considering both experimental model systems as well as human clinical trials.